Phillyrin ameliorates DSS-induced colitis in mice via modulating the gut microbiota and inhibiting the NF-κB/MLCK pathway - Tong Li; Guiqiu Hu; Shoupeng Fu; Di Qin; Zheyu Song (Microbiology Spectrum)
ABSTRACT Phillyrin (PHY), also known as forsythin, is an active constituent isolated from the fruit of Forsythia suspensa (Thunb.) Vahl (Oleaceae). It exhibits anti-inflammatory, anti-viral, and antioxidant properties. However, the precise impact of PHY on colitis induced by dextran sodium sulfate (DSS) and its mechanism remain elusive. The present investigation revealed that PHY (12.5, 25.0, and 50.0 mg/kg) exhibited significant therapeutic efficacy in protecting mice against DSS-induced colitis. This effect was manifested as reduced weight loss, a shortened colon, increased secretion of inflammatory factors, increased intestinal permeability, and an enhanced disease activity index in mice with ulcerative colitis (UC). Molecular investigations have determined that PHY mitigates the nuclear translocation of nuclear factor kappa B, thereby downregulating myosin light-chain kinase-driven myosin light-chain phosphorylation. This mechanism results in the preservation of the integrity of the intestinal barrier. The outcomes of 16S rRNA sequencing suggest that PHY (50 mg/kg) augmented the relative abundance of certain probiotic strains, including Lactobacillaceae and Lachnospiraceae. Additionally, PHY supplementation elevated the short-chain fatty acid contents within the intestinal contents of mice with UC. In conclusion, pre-treatment with PHY may ameliorate the DSS-induced UC in mice by lowering the expression of inflammatory factors, protecting intestinal barrier function, and enhancing the structure of the intestinal flora.IMPORTANCEThe protective effect of phillyrin on DSS-induced colitis was explained for the first time, and the anti-inflammatory effect of phillyrin was demonstrated by fecal microbiota transplantation experiments mainly through intestinal flora.